Low Body Mass Index in Females May Portend Inferior Outcomes After Primary Hip Arthroscopy: A Propensity-Matched Analysis With Minimum 2-Year Follow-up. Issue 2 (February 2022) - Jimenez, Andrew E.; Glein, Rachel M.; Owens, Jade S.; George, Tom; Maldonado, David R.; Saks, Benjamin R.; Lall, Ajay C.; Domb, Benjamin G.
Background: There is a paucity of literature evaluating the effect of low body mass index (BMI) in female patients undergoing primary hip arthroscopy. Purpose: (1) To report minimum 2-year patient-reported outcome scores for female patients with low BMI who underwent primary hip arthroscopy for femoroacetabular impingement syndrome and (2) to compare these results with a propensity-matched control group of female patients with normal BMI. Study Design: Cohort study; Level of evidence, 3 Methods: Data were collected on all female patients who had low BMI (<18.5) and underwent primary hip arthroscopy between April 2008 and January 2019. Patients were excluded if they had a previous hip arthroscopy; had workers' compensation; were unwilling to participate in the study; or had Tönnis osteoarthritis grade >1, acetabular dysplasia, or a previous hip condition. Minimum 2-year patient-reported outcomes were collected for the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score, Hip Outcome Score–Sport Specific Subscale (HOS-SSS), visual analog scale for pain, and satisfaction. The percentage of patients achieving the minimal clinically important difference (MCID), Patient Acceptable Symptom State (PASS), and maximum outcome improvement satisfaction threshold (MOIST) was also recorded. These patients were propensity matched in a 1:2 ratio to female patients with normal BMI for comparison. Results: A total of 43 patients (49 hips) were included with a mean ± SD follow-up of 26.9 ± 8.3 months, age of 24.1 ± 12.6 years, and BMI of 17.7 ± 0.67. These patients demonstrated significant improvement from presurgery to minimum 2-year follow-up for the mHHS, Non-Arthritic Hip Score, HOS-SSS, and visual analog scale ( P < .05). When outcomes were compared with 93 control patients (97 hips), female patients with low BMI demonstrated lower rates of achieving the PASS for the mHHS (61.2% vs 77.3%; P = .041) and HOS-SSS (39.5% vs 57.1%; P = .031). Rates of achieving the MCID and MOIST were similar between the groups ( P > .05). Female patients with low BMI also had higher rates of revision when compared with the control group, but this did not reach statistical significance (14.2% vs 7.2%; P = .171). Conclusion: Female patients with low BMI undergoing primary hip arthroscopy for femoroacetabular impingement syndrome demonstrated significant improvement in patient-reported outcomes at minimum 2-year follow-up. When compared with a propensity-matched control group with normal BMI, these patients demonstrated lower rates of achieving the PASS for the mHHS and HOS-SSS. Low BMI in females undergoing primary hip arthroscopy for FAIS may adversely affect outcomes at short-term follow-up.